IN DEFENSE OF THE FREEDOM OF THE PRESS: THE INDONESIAN PLAYBOY MAGAZINE CASE STUDY - Pulungan, M. Sofyan (Indonesia Law Review, 2014)
One of the most observable achievements in the development of liberal democracy in Indonesia after the fall of the Soeharto’s New Order is the flourishing freedom of the press. One notable case was the Indonesian Playboy magazine and court decisions pertaining to it, which was successful in drawing massive public and even international attention. By thoroughly describing thoughts, feelings, values, and beliefs of various actors involved, this article explains the impacts of liberal democracy experimentation in Indonesia after the amendment of 1945 Constitution. This case has provided an excellent opportunity in observing the rule of law in enforcing the freedom of the press in Indonesia facing social cultural elements strongly adhered to by Indonesian people.